A catalyst for preparing sulfur by oxidation of hydrogen sulfide and preparation method thereof
By using a mixed oxide catalyst with composite oxide and alkyl-based to modify the silicon dioxide, combined with the solution-gel legal preparation technology, the problem of the existing catalysts' activity and selective reduction under the conditions of high water content achieved efficient Hydrogen sulfide selects oxidation reactions.
Patent Information
- Application Number
- CN202310978827.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-08-04
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2043-08-04
AI Technical Summary
The existing hydrogen sulfide selective oxidation catalysts have problems of decreasing catalyst activity and reducing selectivity under high water content conditions, making it difficult to effectively treat high water content hydrogen sulfide gas.
A mixed oxide catalyst including composite oxide and alkyl-modified silica is used, prepared by the sol-gel method, to form large-sized particles with high water resistance and stability, improving the activity and activity of the catalyst under high water content conditions. Selectivity.
Under the conditions of high water content, the catalyst shows a stable and high conversion rate and high selectivity, significantly improves the sulfur recovery rate and product selectivity, and solves the problem of losing the catalyst under high water conditions.
Smart Images

Figure CN117000306B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of catalyst preparation, and in particular relates to a hydrogen sulfide oxidation catalyst for high water content conditions and a preparation method thereof. Background Art
[0002] In industrial production processes, such as natural gas extraction, oil refining, coal chemical industry and shipbuilding, there are a lot of hydrogen sulfide gases that need to be treated. These gases will not only corrode equipment pipelines, but also produce some sulfur oxides, which will further cause acid rain, sulfuric acid mist and other environmental pollution phenomena, endangering human health. The traditional hydrogen sulfide recovery process adopts the Claus process. With the increasing improvement of environmental protection standards, the traditional Claus method is limited by thermodynamic equilibrium, and the sulfur recovery rate is low. The tail gas cannot meet the standards and other problems are becoming increasingly prominent. The Claus derivative process Super Claus has the advantages of simple operation, low equipment construction and operation costs. It is the best way to treat low-concentration acid gas. The core of this process is the selective oxidation of hydrogen sulfide into elemental sulfur catalyst.
[0003] This method can directly oxidize hydrogen sulfide and air into elemental sulfur, using a highly active and highly selective catalyst to reduce the sulfur dioxide produced during the reaction, while reducing the hydrogen sulfide content in the gas after the reaction, and obtaining a higher sulfur recovery rate. The main reactions are as follows:
[0004] 2H2S+O2→2 / nS n +H2O (1)
[0005] 2H2S+3O2→2SO2+2H2O (2)
[0006] S+O2→SO2 (3)
[0007] In this process, reaction (1) is the main reaction and is not restricted by thermodynamic equilibrium. Therefore, theoretically, a very high conversion rate of hydrogen sulfide can be achieved. Reactions (2) and (3) are side reactions, which are highly exothermic and consume a lot of oxygen. They must be controlled by a highly selective and stable catalyst.
[0008] Existing hydrogen sulfide selective oxidation catalysts have problems such as low sulfur yield and catalyst activity being greatly affected by water vapor.
[0009] Chinese patent CN 101380582A discloses a hydrogen sulfide selective oxidation catalyst and process, using TiO2 as a carrier, Fe and Cr as active components, with a hydrogen sulfide conversion rate of 99.5%, a selectivity of 92%, and a sulfur recovery rate of 91.5%. The patent requires that the hydrogen sulfide concentration in the raw acid gas be ≤3%. When the hydrogen sulfide concentration is higher than 3%, the catalyst bed temperature is increased and the selectivity is reduced due to the large amount of heat generated by the reaction. The hydrogen sulfide and sulfur dioxide contents in the gas after the reaction will exceed the limit values required by environmental protection. Therefore, the patent can only be applied to low-concentration hydrogen sulfide acid gas.
[0010] CN200810157750.4 discloses a catalyst and process for selectively oxidizing hydrogen sulfide to elemental sulfur. The catalyst comprises a carrier and an active component, wherein the active component is ferric oxide and / or chromium oxide, and the carrier is a mixed oxide of titanium dioxide and aluminum oxide, wherein the content of titanium dioxide in the carrier is 60% to 95%. The catalyst is used for the reaction of selectively oxidizing hydrogen sulfide to elemental sulfur in a hydrogen sulfide-containing mixed gas. The reaction conditions are: temperature 160 to 280°C, pressure 0.02 to 10.0 MPa, gas space velocity 400 to 2000 h -1 , H2S≤3.0% (V), O2 / H2S (molar ratio) = 0.6-3.0. Since the catalyst uses titanium dioxide as a carrier, it has poor water vapor resistance and can only be used to treat gases with anhydrous or low water content (less than 5%). Summary of the invention
[0011] The purpose of the present invention is to overcome the shortcomings of the prior art and provide a mixed oxide catalyst for selectively oxidizing hydrogen sulfide to sulfur under high water content conditions and a preparation method and application thereof. The mixed oxide catalyst used can obtain stable high conversion rate and high selectivity under high water content conditions.
[0012] The present invention is achieved through the following technical solutions:
[0013] A catalyst for producing sulfur by oxidation of hydrogen sulfide, the catalyst comprising a composite oxide and alkyl-modified silicon dioxide; the mass content of the composite oxide in the catalyst for producing sulfur by oxidation of hydrogen sulfide is 20% to 70%, and the mass content of the alkyl-modified silicon dioxide is 30% to 80%;
[0014] The composite oxide is a composite oxide in which a carrier loads an active metal oxide; wherein the carrier is one or both of TiO2 and SiO2; the active metal oxide is one or more of ferric oxide, cerium dioxide or magnesium oxide; and the mass content of the active metal oxide in the composite oxide is 5% to 30%.
[0015] In the above technical solution, the mass content of the composite oxide in the hydrogen sulfide oxidation sulfur-making catalyst is 30% to 60%.
[0016] In the above technical solution, the carrier is TiO2; the active metal oxide is ferric oxide; and the mass content of the active metal oxide in the composite oxide is 5% to 30%.
[0017] A method for preparing a catalyst for preparing sulfur by oxidation of hydrogen sulfide, the method comprising the following steps:
[0018] Step 1, adding a carrier precursor to an organic solvent, and then adding an active metal precursor to obtain a first mixture; the mass ratio of the active metal precursor to the carrier precursor is 1:(1.96-21.3)
[0019] The carrier precursor is one or both of butyl titanate and tetraethyl silicate;
[0020] The cation in the active metal precursor is selected from Fe 3+ 、Ce 3+ Mg 2+ One or more of; the anion in the active metal precursor is selected from one or more of chloride, nitrate, sulfate or citrate;
[0021] Step 2, adding acid to the first mixture to adjust the pH value to 2.5-3.5, adding deionized water to hydrolyze, to obtain a first mixture after hydrolysis; the mass ratio of the carrier precursor to the deionized water added in the first mixture is 1:(0.05-1);
[0022] Step 3, stirring the first mixture after hydrolysis to form a sol, aging for 36 to 54 hours, and then drying and calcining to obtain a composite oxide;
[0023] Step 4, dispersing the composite oxide into an organic solution to obtain a second mixture;
[0024] Step 5, adding tetraethyl silicate and organosilane to the second mixture, stirring to make them dispersed evenly to obtain a third mixture; the mass ratio of tetraethyl silicate to organosilane is 1:(0.1-0.3);
[0025] The organosilane is one or more of dimethyldiethoxysilane, ethoxyethylsilane or trimethylethoxysilane;
[0026] Step 6, adding ammonia water and deionized water to the third mixture for hydrolysis, stirring to obtain a hydrolyzed third mixture; adjusting the pH value to 9.5-10.5 with ammonia water; the total mass ratio of tetraethyl silicate and organosilane to deionized water is 1:0.05-1;
[0027] Step 7, removing the solvent from the hydrolyzed third mixture to obtain a solid powder, and drying the solid powder to obtain the hydrogen sulfide oxidation sulfur-making catalyst.
[0028] In the above technical solution, in step 1, the carrier precursor is butyl titanate; the cation in the active metal precursor is Fe 3+ . ① The active metal precursor is the corresponding metal salt, and the precursor of the carrier is butyl titanate and tetraethyl silicate; ② The mass ratio of the active metal precursor to the carrier precursor is =1:1.96~21.3; ③ The mass ratio of the active metal oxide to the carrier is 1:2.33~19④ The mass ratio of iron, cerium, and magnesium precursors is 0~1:0~1:0~1; ⑤ The mass ratio of silicon and titanium carriers in the composite oxide is 0~1:0~1; ⑥ The mass ratio of silicon and titanium carrier precursors in the composite oxide is 0~1:0~1; ⑦ When different salts are mixed as precursors, their mass ratio is also 0~1:0~1:0~1.
[0029] In the above technical solution, in step 2, the acid is one or more of acetic acid, hydrochloric acid, and nitric acid, preferably acetic acid; an acid is added to the first mixture to adjust the pH value to 3; and the method of adding deionized water for hydrolysis is to dropwise add deionized water.
[0030] In the above technical solution, in step 3, the aging time is 48 hours; the drying temperature is 100-150°C, preferably 100°C; and the calcination temperature is 400-600°C.
[0031] In the above technical solution, in step 6, 25 wt % ammonia water and deionized water are added to the third mixture for hydrolysis, and stirred for 5 hours to obtain the hydrolyzed third mixture.
[0032] In the above technical solution, in step 7, the process of removing the solvent is carried out by vacuum distillation; the solid powder is dried at 100-150° C. for 12-24 hours to obtain the hydrogen sulfide oxidation sulfur-making catalyst. Preferably, the solid powder is dried at 120° C. for 16 hours to obtain the hydrogen sulfide oxidation sulfur-making catalyst.
[0033] In the above technical solution, the organic solvent is one or more of ethanol solution, methanol solution or acetone.
[0034] A method for preparing sulfur by oxidation of hydrogen sulfide comprises the following steps:
[0035] The reaction gas is preheated to 80-140°C. After preheating, the reaction gas enters an isothermal reactor filled with the hydrogen sulfide oxidation sulfur-making catalyst described in the above technical solution. The reaction temperature is controlled at 180-240°C and the reaction feed volume space velocity is 500-3000h-1 , the reaction pressure is 0.1~1MPa (gauge pressure), and the gas after the reaction collects sulfur to obtain the product;
[0036] The concentration of H2S in the preheated reaction gas is 0.5% to 3 vol%, the content of water vapor is 10 vol% to 40 vol%, and the volume ratio of oxygen to H2S is 0.5 to 1:1, preferably 0.6 to 0.8:1.
[0037] The advantages and beneficial effects of the present invention are:
[0038] The method of the present invention uses a catalyst for the oxidation of hydrogen sulfide to produce sulfur, and the catalyst for the oxidation of hydrogen sulfide to produce sulfur includes a composite oxide and an alkyl-modified silica. The composite oxide has the activity of selectively oxidizing hydrogen sulfide to produce elemental sulfur, and the silica is an alkyl-modified silica catalyst, which can accelerate the desorption of water on the catalyst surface and inhibit the competitive adsorption of water vapor and hydrogen sulfide. The composite oxide is used alone in the selective oxidation of hydrogen sulfide to produce elemental sulfur, and has the characteristics of high catalytic activity and good stability in the treatment of reaction gas without water vapor. However, in the case where the feed gas contains water vapor, the gas needs to be pretreated to remove the water in the reaction system. The method of the present invention uses a catalyst for the oxidation of hydrogen sulfide to produce sulfur, and under suitable ratio conditions, the activity of the reaction system and the selectivity of the target product are equivalent to those after pretreatment and dehydration, and the activity and selectivity are significantly improved compared with the use of the composite oxide catalyst alone. The problem that the composite oxide catalyst is easily deactivated under the condition of water vapor feed is solved, and the stability of the catalyst is improved. BRIEF DESCRIPTION OF THE DRAWINGS
[0039] Figure 1 It is a graph showing the stability evaluation results of the catalyst prepared in Example 2 of the present invention and the catalyst in Comparative Example 1.
[0040] Figure 2 The water contact angle test diagrams of the catalysts obtained in the embodiments of the present invention and the comparative examples, wherein: (a) before sol-gel reaction (b) after sol-gel reaction (c) outer surface of immersion method (d) inner surface of immersion method (e) physical mixing method.
[0041] For ordinary technicians in this field, other relevant drawings can be obtained based on the above drawings without any creative work. DETAILED DESCRIPTION
[0042] In order to enable those skilled in the art to better understand the technical solution of the present invention, the technical solution of the present invention is further described below in conjunction with specific embodiments.
[0043] Example 1
[0044] At room temperature, 7.67 g of butyl titanate was added dropwise to 50 mL of ethanol, stirred evenly, and then 0.5 g of ferric nitrate nonahydrate was added. Acetic acid was added to adjust the pH value to 3, stirred for 1 hour, and then 2.5 mL of deionized water was added dropwise, and stirring was continued for 5 hours to fully hydrolyze to form a sol. After aging at room temperature for 48 hours, the sol was dried at 100°C for 12 hours and calcined at 500°C for 3 hours to obtain a composite oxide. The composite oxide was dispersed in 50 mL of ethanol solution, 5.54 g of tetraethyl silicate and 1.0 g of dimethyldiethoxysilane were added dropwise, stirred well to make it evenly dispersed, and then ammonia water was added to adjust the pH value to 10, and 4 mL of deionized water was added dropwise for hydrolysis, and stirring was continued for 5 hours. After removing the solvent, a solid powder was obtained, and the solid powder was dried at 120°C for 12 hours to obtain the hydrogen sulfide oxidation sulfur-making catalyst A1.
[0045] Based on the total mass of the hydrogen sulfide oxidation sulfur-making catalyst, the composite oxide (whose composition is 10wt% Fe2O3-90wt% TiO2) accounts for 50wt%; the alkyl-modified silica is methyl-modified silica, accounting for 50wt%.
[0046] Example 2
[0047] At room temperature, 7.67 g of butyl titanate was added dropwise to 50 mL of ethanol, and after stirring evenly, 0.5 g of ferric nitrate nonahydrate was added, and acetic acid was added to adjust the pH value to 3. After stirring for 1 hour, 2.5 mL of deionized water was added dropwise, and stirring was continued for 5 hours to fully hydrolyze to form a sol. After aging at room temperature for 48 hours, it was dried at 100°C for 12 hours and calcined at 500°C for 3 hours to obtain a composite oxide; the composite oxide was dispersed in 50 mL of ethanol solution, 2.67 g of tetraethyl silicate and 0.2 g of dimethyldiethoxysilane were added dropwise, and after fully stirring to make it evenly dispersed, ammonia water was added to adjust the pH to 10, and 2 mL of deionized water was added dropwise for hydrolysis, and stirring was continued for 5 hours; after removing the solvent, a solid powder was obtained, and the solid powder was dried at 120°C for 12 hours to obtain the hydrogen sulfide oxidation sulfur-making catalyst A2.
[0048] Based on the total mass of the hydrogen sulfide oxidation sulfur-making catalyst, the composite oxide group (which is 10wt% Fe2O3-90wt% TiO2) accounts for 70%; the alkyl-modified silica is methyl-modified silica, accounting for 30%.
[0049] Example 3
[0050] At room temperature, 5.96 g of butyl titanate and 1.38 g of tetraethyl silicate were added dropwise to 50 mL of ethanol, stirred evenly, and then 0.5 g of ferric nitrate nonahydrate was added. Acetic acid was added to adjust the pH value to 3, stirred for 1 hour, and then 3 mL of deionized water was added dropwise, and stirring was continued for 5 hours to fully hydrolyze to form a sol. After aging at room temperature for 48 hours, the sol was dried at 100°C for 12 hours and calcined at 500°C for 3 hours to obtain a composite oxide. The composite oxide was dispersed in 50 mL of ethanol solution, 2.67 g of tetraethyl silicate and 0.2 g of dimethyldiethoxysilane were added dropwise, stirred well to make it evenly dispersed, and then ammonia water was added to adjust the pH to 10, and 2 mL of deionized water was added dropwise for hydrolysis, and stirring was continued for 5 hours. After removing the solvent, a solid powder was obtained, and the solid powder was dried at 120°C for 12 hours to obtain the hydrogen sulfide oxidation sulfur-making catalyst A3.
[0051] Based on the total mass of the hydrogen sulfide oxidation sulfur-making catalyst, the composite oxide (whose composition is 10wt% Fe2O3-70wt% TiO2-20wt% SiO2) accounts for 70%; the alkyl-modified silica is methyl-modified silica, accounting for 30%.
[0052] Example 4
[0053] At room temperature, 2.55 g of butyl titanate and 0.6 g of tetraethyl silicate are added dropwise to 50 mL of ethanol, stirred evenly, and then 0.5 g of ferric nitrate nonahydrate is added, and acetic acid is added to adjust the pH value to 3. After stirring for 1 hour, 1.5 mL of deionized water is added dropwise, and stirring is continued for 5 hours to fully hydrolyze to form a sol. After aging at room temperature for 48 hours, it is dried at 100°C for 12 hours and calcined at 500°C for 3 hours to obtain a composite oxide; the composite oxide is dispersed in 50 mL of ethanol solution, 6.23 g of tetraethyl silicate and 0.5 g of dimethyldiethoxysilane are added dropwise, and after fully stirring to make it dispersed evenly, ammonia water is added to adjust the pH to 10, and 4.5 mL of deionized water is added dropwise for hydrolysis, and stirring is continued for 5 hours; after removing the solvent, a solid powder is obtained, and the solid powder is dried at 120°C for 12 hours to obtain the hydrogen sulfide oxidation sulfur-making catalyst A4.
[0054] Based on the total weight of the hydrogen sulfide oxidation sulfur-making catalyst, the composite oxide composition is 10% Fe2O3-70% TiO2-20% SiO2 (wt.), accounting for 30%, and the silicon dioxide is methyl-modified silicon dioxide, accounting for 70%.
[0055] Example 5
[0056] At room temperature, 6.8 g of butyl titanate was added dropwise to 50 mL of ethanol, and after stirring, 0.5 g of ferric nitrate nonahydrate and 0.5 g of cerium nitrate hexahydrate were added, and acetic acid was added to adjust the pH value to 3. After stirring for 1 hour, 2 mL of deionized water was added dropwise, and stirring was continued for 5 hours to fully hydrolyze to form a sol. After aging at room temperature for 48 hours, it was dried at 100°C for 12 hours and calcined at 500°C for 3 hours to obtain a composite oxide; the composite oxide was dispersed in 50 mL of ethanol solution, 5.54 g of tetraethyl silicate and 1.0 g of ethyltrimethoxysilane were added dropwise, and after fully stirring to make it dispersed evenly, ammonia water was added to adjust the pH to 10, and 4 mL of deionized water was added dropwise for hydrolysis, and stirring was continued for 5 hours; after removing the solvent, a solid powder was obtained, and the solid powder was dried at 120°C for 12 hours to obtain the hydrogen sulfide oxidation sulfur-making catalyst A5.
[0057] Based on the total mass of the hydrogen sulfide oxidation sulfur-making catalyst and the total mass of the mixed component catalyst, the composite oxide composition is 10% Fe2O3-10% CeO2-80% TiO2 (wt.), accounting for 50%, and the silicon dioxide is ethyl-modified silicon dioxide, accounting for 50%.
[0058] Example 6
[0059] At room temperature, 5.4 g of butyl titanate was added dropwise to 50 mL of acetone, and after stirring evenly, 1.05 g of magnesium nitrate hexahydrate and 0.6 g of cerium nitrate hexahydrate were added, and acetic acid was added to adjust the pH value to 3. After stirring for 1 hour, 2 mL of deionized water was added dropwise, and stirring was continued for 5 hours to fully hydrolyze to form a sol. After aging at room temperature for 48 hours, it was dried at 100°C for 12 hours and calcined at 500°C for 3 hours to obtain a composite oxide; the composite oxide was dispersed in 50 mL of ethanol solution, 6.64 g of tetraethyl silicate and 1.2 g of ethyltrimethoxysilane were added dropwise, and after fully stirring to make it evenly dispersed, ammonia water was added to adjust the pH to 10, and 4 mL of deionized water was added dropwise for hydrolysis, and stirring was continued for 5 hours; after removing the solvent, a solid powder was obtained, and the solid powder was dried at 120°C for 12 hours to obtain the hydrogen sulfide oxidation sulfur-making catalyst A6.
[0060] Based on the total mass of the hydrogen sulfide oxidation sulfur-making catalyst, the composite oxide composition is 5% MgO-15% CeO2-80% TiO2 (wt.), accounting for 40%, and the silicon dioxide is ethyl-modified silicon dioxide, accounting for 60%.
[0061] Example 7
[0062] At room temperature, 6.8 g of butyl titanate was added dropwise to 50 mL of methanol, and after stirring evenly, 0.5 g of ferric nitrate nonahydrate and 1.28 g of magnesium nitrate hexahydrate were added, and acetic acid was added to adjust the pH value to 3. After stirring for 1 hour, 2 mL of deionized water was added dropwise, and stirring was continued for 5 hours to fully hydrolyze to form a sol. After aging at room temperature for 48 hours, it was dried at 100°C for 12 hours and calcined at 500°C for 3 hours to obtain a composite oxide; the composite oxide was dispersed in 50 mL of ethanol solution, 5.54 g of tetraethyl silicate and 1.0 g of dimethyldiethoxysilane were added dropwise, and after fully stirring to make it evenly dispersed, ammonia water was added to adjust the pH to 10, and 4 mL of deionized water was added dropwise for hydrolysis, and stirring was continued for 5 hours; after removing the solvent, a solid powder was obtained, and the solid powder was dried at 120°C for 12 hours to obtain the hydrogen sulfide oxidation sulfur-making catalyst A7.
[0063] Based on the total weight of the hydrogen sulfide oxidation sulfur-making catalyst, the composite oxide composition is 10% MgO-10% Fe2O3-80% TiO2 (wt.), accounting for 50%, and the silicon dioxide is methyl-modified silicon dioxide, accounting for 50%.
[0064] Example 8
[0065] At room temperature, 8.67 g of butyl titanate was added dropwise to 50 mL of ethanol, and after stirring, 0.3 g of cerium nitrate hexahydrate, 0.3 g of ferric nitrate nonahydrate, and 0.77 g of magnesium nitrate hexahydrate were added, and hydrochloric acid was added to adjust the pH value to 3. After stirring for 1 hour, 2.5 mL of deionized water was added dropwise, and stirring was continued for 5 hours to fully hydrolyze to form a sol. After aging at room temperature for 48 hours, it was dried at 100°C for 12 hours and calcined at 500°C for 3 hours to obtain a composite oxide; the composite oxide was dispersed in 50 mL of ethanol solution, 4.4 g of tetraethyl silicate and 0.8 g of dimethyldiethoxysilane were added dropwise, and after fully stirring to make it dispersed evenly, ammonia water was added to adjust the pH to 10, and 3.5 mL of deionized water was added dropwise for hydrolysis, and stirring was continued for 5 hours; after removing the solvent, a solid powder was obtained, and the solid powder was dried at 120°C for 12 hours to obtain the hydrogen sulfide oxidation sulfur-making catalyst A8.
[0066] Based on the total mass of the hydrogen sulfide oxidation sulfur-making catalyst, the composite oxide composition is 5% CeO2-5% MgO-5% Fe2O3-85% TiO2 (wt.), accounting for 60%, and the silicon dioxide is methyl-modified silicon dioxide, accounting for 40%.
[0067] Comparative Example 1
[0068] The reaction results are shown in Table 1.
[0069] Comparative Example 2
[0070] The reaction results are shown in Table 1.
[0071] Comparative Example 3
[0072] At room temperature, 7.67 g of butyl titanate was added to 50 mL of ethanol, stirred evenly, and then 0.5 g of ferric nitrate nonahydrate was added. Acetic acid was added to adjust the pH value to 3, stirred for 1 h, and then 2.5 mL of deionized water was added. Stirring was continued for 5 h to fully hydrolyze to form a sol. After aging at room temperature for 48 h, it was dried at 100 ° C for 12 h and calcined at 500 ° C for 3 h to obtain a composite oxide. To 50 mL of ethanol solution, 5.54 g of tetraethyl silicate and 1.0 g of dimethyl Diethoxysilane is fully stirred to make it evenly dispersed, and then ammonia water is added to adjust the pH to 10, and 4 mL of deionized water is added dropwise for hydrolysis, and stirring is continued for 5 hours. Solid powder is obtained by vacuum distillation at 50°C, and the solid powder is dried at 120°C for 12 hours to obtain hydrophobic silica. The obtained composite oxide and hydrophobic silica powder are ground separately and mixed and ground in a mass ratio of 1:1, and then tableted using a tablet press, and then crushed and sieved to obtain the hydrogen sulfide oxidation sulfur-making catalyst B3.
[0073] The composition and ratio of the composite oxide and the hydrophobic silica are the same as those in Example 1, except that the composite oxide and the hydrophobic silica are prepared by a physical mixing method.
[0074] Comparative Example 4
[0075] At room temperature, 7.67 g of butyl titanate was added dropwise to 50 mL of ethanol, and after stirring evenly, 0.5 g of ferric nitrate nonahydrate was added, and acetic acid was added to adjust the pH value to 3. After stirring for 1 hour, 2.5 mL of deionized water was added dropwise, and stirring was continued for 5 hours to fully hydrolyze to form a sol. After aging at room temperature for 48 hours, it was dried at 100°C for 12 hours and calcined at 500°C for 3 hours to obtain a composite oxide; the obtained composite oxide was added to 50 mL of aqueous solution, 5.54 g of tetraethyl silicate and 1.0 g of dimethyldiethoxysilane were added dropwise, and after fully stirring to make it evenly dispersed, stirring was continued for 5 hours, and solid powder was obtained by reduced pressure distillation at 70°C, which was dried at 120°C for 24 hours to obtain the hydrogen sulfide oxidation sulfur-making catalyst B4.
[0076] The composition and ratio of the composite oxide to silicon dioxide are the same as those in Example 1, except that the composite oxide is prepared by an impregnation method. The hydrophobic silicon dioxide is loaded on the composite oxide.
[0077] Comparative Example 5
[0078] Commercial catalyst HSO-35 was used. The reaction results are shown in Table 1.
[0079] All catalysts in the examples and comparative examples were evaluated using the following method:
[0080] Under normal industrial conditions, hydrogen sulfide gas is accompanied by water vapor. In order to simulate the actual situation in the laboratory, hydrogen sulfide gas, water vapor and air are divided into three gas mixtures and then enter the reactor for evaluation.
[0081] The reaction gas is preheated to 80-140°C. After preheating, the reaction gas enters an isothermal reactor filled with the corresponding catalyst. The reaction temperature is controlled and the reaction feed volume space velocity is 3000h -1 The reaction pressure is 0.1 MPa (gauge pressure), and the gas after the reaction collects sulfur to obtain the product; wherein the reaction temperature is controlled as follows: 180°C for Examples 1 to 5, and 200°C, 220°C, and 240°C for Examples 6, 7, and 8, respectively.
[0082] The concentration of H2S in the preheated reaction gas is 1 vol%, the content of water vapor is 40 vol%, and the volume ratio of oxygen to H2S is 0.6-1:1.
[0083] The results are shown in Table 1.
[0084] Hydrogen sulfide conversion rate Selective S S The calculation formula of sulfur yield S is as follows:
[0085]
[0086]
[0087]
[0088] Table 1 Reaction performance of catalysts in the examples
[0089]
[0090]
[0091] Example 9
[0092] The catalyst of Example 1 was used for further evaluation experiments.
[0093] The catalyst evaluation test was carried out in an isothermal fixed-bed reactor at 200 °C for 500 h. -1 , 0.1MPa, H2S content of 0.5-3%, oxygen to hydrogen sulfide ratio of 0.6. Water content of 10-40%, mixed with hydrogen sulfide and oxygen, preheated by electric heater, enters the reactor for selective oxidation reaction. The reaction performance results under different H2S concentrations and different water contents are shown in Table 2.
[0094] Table 2 Reaction performance of catalyst in Example 9 under different water content and H2S concentration conditions
[0095] Temperature(℃) <![CDATA[H2S(%)]]> Water content (%) <![CDATA[H2S conversion rate (%)]]> <![CDATA[S S Selectivity (%)]]> 200 0.5 40 99.7 99 200 2 40 97.4 99.2 200 3 40 95 99.7 200 1 10 98.8 99.4 200 1 20 98.5 99.1 200 1 30 98.5 99 200 1 40 98.2 99
[0096] The long-term stability evaluation of Example 1 and Comparative Example 1 was carried out under the conditions of reaction temperature 180°C, 1% H2S, 40% water content, and 0.1Mpa. The evaluation time was 300h. The conversion rate data are as follows: Figure 1 shown.
[0097] ① Adding alkyl-modified silica can improve the water resistance of the catalyst. Compared with the catalyst prepared in the comparative example without adding alkyl-modified silica, its water contact angle is higher and has higher water resistance. In comparative example 1, the catalyst is hydrophilic and is easily poisoned and deactivated in the presence of water vapor. After adding alkyl-modified silica, the water resistance of the catalyst can be greatly improved, and the stability of the catalyst can be improved.
[0098] ② The catalyst formed by simple physical mixing (Comparative Example 3) is mixed only by physical contact, and its dispersion degree is uneven, and the particle size is large, and it is impossible to achieve uniform dispersion of alkyl-modified silica at a smaller size.
[0099] ③ When using the impregnation method (Comparative Example 4) to prepare the catalyst, a suitable carrier skeleton is required. It cannot be effectively contacted during the impregnation process, the degree of impregnation and the loading amount are limited, and catalyst migration and desorption may occur during use. When the prepared catalyst is used at high temperature, the loaded components may fall off the carrier and affect the effect.
[0100] ④ During the preparation process of the sol-gel method (Examples 1 to 8), effective contact can be formed, and a good contact form is formed around the skeleton. The similar chemical bonding method can form a more stable skeleton. The modification of silica by alkyl groups can effectively remove water vapor and has high selectivity, thereby significantly improving the catalytic activity.
[0101] like Figure 2 As shown in Figure 2, the water contact angle of the catalyst obtained by the sol-gel method is 126° ( Figure 2 (a)), showing hydrophobicity, and its water contact angle can still reach 124° after 300 hours of stability test ( Figure 2 (b)), indicating that it has stable hydrophobic properties; the outer surface of the catalyst obtained by the impregnation method is 115° ( Figure 2 (c)), which is hydrophobic, but its inner surface water contact angle is 30° ( Figure 2 (d)) is hydrophilic; the water contact angle of the catalyst obtained by physical mixing method is 55° ( Figure 2(e)), the surface is unevenly dispersed and thus there is a hydrophilic surface. Therefore, overall, the catalyst obtained by the sol-gel method has better water resistance and a more uniform surface.
[0102] Relational terms such as “first” and “second” and the like are merely used to distinguish one component from another having the same name, but do not necessarily require or imply any such actual relationship or order between these components.
[0103] The present invention is described above by way of example. It should be noted that, without departing from the core of the present invention, any simple deformation, modification or other equivalent replacement that can be made by those skilled in the art without inventive effort falls within the protection scope of the present invention.
Claims
1. A method for preparing a catalyst for preparing sulfur by oxidation of hydrogen sulfide, characterized in that: The following steps are involved: Step 1, adding a carrier precursor to an organic solvent, and then adding an active metal precursor to obtain a first mixture; the mass ratio of the active metal precursor to the carrier precursor is 1:(1.96-21.3); The carrier precursor is one or both of butyl titanate and tetraethyl silicate; The cation in the active metal precursor is selected from Fe 3+ 、Ce 3+ Mg 2+ One or more of; the anion in the active metal precursor is selected from one or more of chloride, nitrate, sulfate or citrate; Step 2, adding acid to the first mixture to adjust the pH value to 2.5-3.5, adding deionized water to hydrolyze, and obtaining a first mixture after hydrolysis; the mass ratio of the carrier precursor to the deionized water added in the first mixture is 1:(0.05-1); Step 3, stirring the first mixture after hydrolysis to form a sol, aging for 36 to 54 hours, and then drying and calcining to obtain a composite oxide; Step 4, dispersing the composite oxide into an organic solvent to obtain a second mixture; Step 5, adding tetraethyl silicate and organosilane to the second mixture, stirring to make them dispersed evenly to obtain a third mixture; the mass ratio of tetraethyl silicate to organosilane is 1: (0.1-0.3); The organosilane is one or more of dimethyldiethoxysilane, ethoxyethylsilane or trimethylethoxysilane; Step 6, adding ammonia water and deionized water to the third mixture for hydrolysis, stirring to obtain a hydrolyzed third mixture; adjusting the pH value to 9.5-10.5 with ammonia water; the total mass ratio of tetraethyl silicate and organosilane to deionized water is 1:0.05-1; Step 7, removing the solvent from the hydrolyzed third mixture to obtain a solid powder, and drying the solid powder to obtain the hydrogen sulfide oxidation catalyst for sulfur production; The organic solvent is one or more of ethanol solution, methanol solution or acetone.
2. The method for preparing a catalyst for preparing sulfur by oxidation of hydrogen sulfide according to claim 1, characterized in that: In step 1, the carrier precursor is butyl titanate; the cation in the active metal precursor is Fe 3+ .
3. The method for preparing a catalyst for preparing sulfur by oxidation of hydrogen sulfide according to claim 1, characterized in that: In step 2, the acid is one or more of acetic acid, hydrochloric acid, and nitric acid; an acid is added to the first mixture to adjust the pH value to 3; and the method of adding deionized water for hydrolysis is to dropwise add deionized water.
4. The method for preparing a catalyst for preparing sulfur by oxidation of hydrogen sulfide according to claim 3, characterized in that: In the step 2, the acid is acetic acid.
5. The method for preparing a catalyst for preparing sulfur by oxidation of hydrogen sulfide according to claim 1, characterized in that: In step 3, the aging time is 48 hours; the drying temperature is 100-150° C.; and the calcination temperature is 400-600° C.
6. The method for preparing a catalyst for preparing sulfur by oxidation of hydrogen sulfide according to claim 1, characterized in that: In step 3, the drying temperature is 100°C.
7. The method for preparing a catalyst for preparing sulfur by oxidation of hydrogen sulfide according to claim 1, characterized in that: In the step 6, 25 wt % ammonia water and deionized water are added to the third mixture for hydrolysis, and the mixture is stirred for 5 hours to obtain a hydrolyzed third mixture.
8. The method for preparing a catalyst for preparing sulfur by oxidation of hydrogen sulfide according to claim 1, characterized in that: In the step 7, the process of removing the solvent is carried out by vacuum distillation; the solid powder is dried at 100-150° C. for 12-24 h to obtain the hydrogen sulfide oxidation sulfur-making catalyst.
9. The method for preparing a catalyst for preparing sulfur by oxidation of hydrogen sulfide according to claim 1, characterized in that: In the step 7, the solid powder is dried at 120° C. for 16 h to obtain the hydrogen sulfide oxidation sulfur-making catalyst.
10. The method for preparing a catalyst for preparing sulfur by oxidation of hydrogen sulfide according to claim 1, characterized in that: The hydrogenation of sulfide to produce sulfur catalyst prepared by the preparation method comprises a composite oxide and alkyl-modified silicon dioxide; the mass content of the composite oxide in the hydrogenation of sulfide to produce sulfur catalyst is 20% to 70%, and the mass content of the alkyl-modified silicon dioxide is 30% to 80%; The composite oxide is a composite oxide in which a carrier loads an active metal oxide; wherein the carrier is one or both of TiO2 or SiO2; the active metal oxide is one or more of ferric oxide, cerium dioxide or magnesium oxide; and the mass content of the active metal oxide in the composite oxide is 5% to 30%.
11. The method for preparing a catalyst for preparing sulfur by oxidation of hydrogen sulfide according to claim 10, characterized in that: The mass content of the composite oxide in the hydrogen sulfide oxidation sulfur-making catalyst prepared by the preparation method is 30% to 60%.
12. The method for preparing a catalyst for preparing sulfur by oxidation of hydrogen sulfide according to claim 10, characterized in that: The hydrogen sulfide oxidation sulfur-making catalyst prepared by the preparation method comprises the following: the carrier is TiO2; the active metal oxide is ferric oxide; and the mass content of the active metal oxide in the composite oxide is 5% to 30%.
13. A method for preparing sulfur by oxidation of hydrogen sulfide, characterized in that: The following steps are involved: Preheat the reaction gas to 80-140°C, and after preheating, the reaction gas enters an isothermal reactor filled with the hydrogen sulfide oxidation sulfur-making catalyst prepared by any method of claims 1-12, and the reaction temperature is controlled at 180-240°C, and the reaction feed volume space velocity is 500-3000h -1 The reaction pressure is 0.1~1MPa, and the gas after the reaction collects sulfur to obtain the product; The concentration of H2S in the preheated reaction gas is 0.5% to 3 vol%, the content of water vapor is 10 vol% to 40 vol%, and the volume ratio of oxygen to H2S is 0.5 to 1:
1.
14. The method for preparing sulfur by oxidation of hydrogen sulfide according to claim 13, characterized in that: The volume ratio of oxygen to H2S is 0.6~0.8:1.
Citation Information
Patent Citations
Catalyst for selective oxidation of sulfureted hydrogen into elemental sulfur and reaction process thereof
CN101380582A
Adsorptive catalyst and preparation method and application thereof as well as air purification device, and air purification method and application thereof
CN104941571A
Catalyst having macro-porous structure and used for production of sulfur through selective oxidation of H2S, and preparation method thereof
CN105126848A